Hyperbaric oxygen therapy is as effective as dexamethasone in the treatment of TNBS-E-induced experimental colitis - ATUĞ, ÖZLEN (SPRINGER, 2008)
Introduction Hyperbaric oxygen (HBO) has been demonstrated to be useful as an adjunctive therapy for Crohn's disease. In the present study, HBO was tested as a treatment for trinitrobenzenesulfonic acid-ethanol (TNBS-E)-induced distal colitis, and its effects were compared with dexamethasone therapy. Methods A total of 48 Sprague-Dawley rats were separated into six groups: the control, and those treated with vehicle, TNBS-E, HBO, dexamethasone, or combined HBO + dexamethasone. The HBO treatment group was exposed to 100% HBO at 2 ATM for 75 min twice daily at 6-h intervals in a HBO chamber, both on the day of colitis induction and 3 days thereafter. Treatment with intraperitoneal dexamethasone twice daily was started 1 h before the induction of colitis and was continued for 7 days in the dexamethasone group. The rats were decapitated 8 days after the induction of colitis, and the colonic tissue wet weight, macroscopic and microscopic lesion score, and tissue myeloperoxidase (MPO) activity were determined. Results HBO therapy decreased the activity of experimental colitis measured by the tissue wet weight, macroscopic score, microscopic score, and MPO activity. The dexamethasone treatment significantly reduced the colitis activity as determined by the tissue MPO activity and wet weight. There were also decreases in the macroscopic and microscopic activity scores with the dexamethasone therapy; however, these changes were not statistically significant. The combined therapy with HBO and dexamethasone provided no additional benefit over HBO therapy alone. Conclusion HBO therapy can be a valuable therapeutic option in treatment of patients with inflammatory bowel disease. HBO therapy in the refractory patients deserves further, larger clinical studies.
Keywords: Hyperbaric oxygen therapy; dexamethasone; TNBS-E; experimental colitis; inflammatory bowel disease; PERIANAL CROHNS-DISEASE; ACID-INDUCED COLITIS; ULCERATIVE-COLITIS; DOUBLE-BLIND; METRONIDAZOLE; RAT; CIPROFLOXACIN; PROTECTION; DAMAGE; TRIAL